PTH-042 Outcomes of endoscopic resection of recurrent colorectal lesions treated at a uk tertiary referral centre. (17th June 2017) - Emmanuel, A; Gulati, S; Burt, M; Hayee, B; Haji, A
Abstract : Introduction: Endoscopic resection of large colorectal lesions, especially by piecemeal EMR, carries a significant risk of recurrence. Although several series examine the outcomes and risk of recurrence following endoscopic resection, few focus on the outcomes of patients being treated for recurrence after initial expert resection, and these mostly focus on one technique to deal with recurrence. We evaluated the outcomes after recurrence of colorectal lesions after apparent successful endoscopic resection in a specialised UK tertiary institution employing a range of resection techniques. Method: Consecutive patients who underwent endoscopic resection of colorectal lesions≥2 cm were included. All lesions were assessed with magnification chromoendoscopy supplemented by colonoscopic ultrasound in selected cases. A lesion specific approach was used to decide on resection technique. Outcomes were evaluated for patients treated for recurrent lesions. Results: Of 396 colorectal lesions≥2 cm successfully resected at our institution, recurrence occurred in 50. 36% of these patients had already had a mean of 1.6 previous failed attempts at resection prior to referral to our institution, and 66% had had either a failed attempt at resection or extensive sampling involving ≥6 biopsies or tattoo placed under the lesion. 69% of patients were successfully treated with further endoscopic resection and avoided surgery. 27 patients had endoscopic resection of a recurrence larger than 20 mm, with a mean lesion size of 48.3+/-19.1 mm. Techniques used were EMR (n=16), ESD (n=2), Hybrid ESD and EMR (n=9). The remaining lesions<2 cm were resected using EMR. A mean of 1.4+/-0.75 procedures were required to achieve successful endoscopic treatment of recurrence. 24 patients who were ultimately successfully treated with endoscopic resection required a single further endoscopic resection after recurrence, 10 patients required 2 or more further resections. 8 patients required surgery, 4 as a result of developing invasive adenocarcinoma with the recurrence. There were no perforations as a result of endoscopic resection of recurrent lesions and only 1 patient was readmitted with post-procedural bleeding which was managed conservatively. Conclusion: These data demonstrate the challenges of an advanced endoscopic resection service in much of western practice where patients with recurrent lesions represent a particularly complex cohort, most of whom have already had extensive prior manipulation or attempts at resection. Familiarity with a range of resection techniques and appropriate equipment is essential to successfully treat recurrent lesions in this group with endoscopic resection, which can be achieved in the majority of patients without significant complications. Disclosure of Interest: None Declared